Hethitica - Žepič, Vid (Pravnik, 2023)
The reissue of the scholarly article by the esteemed Slovene academic, Professor Viktor Korošec (1899-1985), titled Hethitica: A Contribution to the Development of Hittite Law, delves into the evolution and critical problematic aspects of the legal framework governing the Hittites, the ancient Anatolian civilization that peaked in the 14th century BC. The accompanying foreword written by professor dr. Janez Kranjc, outlines Korošec’s extensive scientific contributions, primarily consisting of articles on oriental legal studies. Despite the significant progress in hittitology over the past six decades, Korošec’s insights remain relevant today, as evidenced by citations of his works in contemporary hittitological scholarship.
Keywords: Hetiti; hetitologija; Hittites; hittitology; Knjižne recenzije; legal history; oriental law; orientalska prava; pravna zgodovina; Viktor Korošec